Pemaknaan Alam Dalam Karya I Made Arya Palguna - Suyasa, I Nyoman (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2014)
Interactions between humans and nature around a lot to do with the creation of works of art both in terms of motivation and the creation of the result later. Nature provides its own meaning for each artist to be disclosed into work, Made Arya Palguna are artists who give their own meaning to nature admired to be disclosed into works of art. The relationship between individuals (Palguna) with nature in orbit consciousness as human beings living in the traditional and modern voltage. Palguna familiar and even close to the surrounding nature, but it does not cause admiration closeness to the outward forms, but the essence in it. More interpret nature as a part of the creative process to uncover the hidden meaning in nature.Keywords: nature, meaning, and Palguna